The Reliability of the GNRB® Knee Arthrometer in Measuring ACL Stiffness and Laxity: Implications for Clinical Use and Clinical Trial Design - Kayla Smith; Nicole Miller; Steve Laslovich (International Journal of Sports Physical Therapy)
# Background